Audiovisual Translation in the Basque Country: The Case of Basque Television-Euskal Telebista (ETB) - Barambones, Josu; Merino, Raquel; Uribarri, Ibon (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2012)
Recent historical translation research done on Basque state-owned television shows that while the Basque-speaking channel has used dubbed translation of children’s programmes to promote and standardize the use of Basque, the Spanish-speaking channel has competed in the wider market of Spanish broadcasting channels with fiction for adults. The choice of products to be broadcast for diverse target audiences clearly reflects a diglossic situation in terms of language distribution but it also serves to illustrate government language planning policies. Since Basque television is controlled by political instances (power), manipulation and ideology clearly have an influence both selecting the programmes and controlling the type of (Basque) language used when translating and dubbing imported products.